Association of Allelic Variation in Genes Mediating Aspects of Energy Homeostasis with Weight Gain during Administration of Antipsychotic Drugs (CATIE Study) - Tiwari, Hemant K.; Patki, Amit; Lieberman, Jeffrey; Stroup, T. Scott; Allison, David B.; Leibel, Rudolph L.; Chung, Wendy K. (Frontiers in Genetics, 2011)
Antipsychotic drugs are widely used in treating schizophrenia, bipolar disorder, and other psychiatric disorders. Many of these drugs, despite their therapeutic advantages, substantially increase body weight. We assessed the association of alleles of 31 genes implicated in body weight regulation with weight gain among patients being treated with specific antipsychotic medications in the CATIE trial, we found that rs2237988 in ATP-binding cassette subfamily C member 8 (ABCC8) , and rs11643744 and rs9922047 in Fat Mass and Obesity Associated (FTO) were associated with such weight gain.